2023
DOI: 10.1029/2023gl105708
|View full text |Cite
|
Sign up to set email alerts
|

Solar Irradiance Modulates the Asian Summer Monsoon—ENSO Relationship Over the Last Millennium

Xiaojing Du,
Sylvia Dee,
Jun Hu
et al.

Abstract: The Asian summer monsoon (ASM) is teleconnected to the El Niño Southern Oscillation (ENSO), but this relationship is nonstationary and has shifted significantly in recent decades. Characterizing the drivers of such shifts is crucial for improving ASM prediction and extreme event preparedness. Paleoclimate records indicate a link between ASM strength and solar activity on multidecadal‐to‐centennial timescales, but 20th‐century data are too short to test mechanisms. Here we evaluate how solar irradiance influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…For example, Mehta and Lau (1997) proposed that solar irradiance could impact the ENSO-ISM relationship over multidecadal time scales, as a long-lived, above-normal irradiance anomaly would amplify the contrast in thermal conditions between land and sea, leading to an intensification of monsoon winds and above-normal rainfall over India. Recent paleoclimate evidence confirms this, suggesting that during periods of high total solar irradiance, the ENSO-ISM correlation is strengthened and the ENSO-EASM correlation is weakened (Du et al, 2023). In addition, Narasimha and Bhattacharyya (2010) showed ENSO connections with solar activity, and suggested that the influence of solar irradiance on the ISM is indirectly applied via the ENSO teleconnection.…”
mentioning
confidence: 79%
“…For example, Mehta and Lau (1997) proposed that solar irradiance could impact the ENSO-ISM relationship over multidecadal time scales, as a long-lived, above-normal irradiance anomaly would amplify the contrast in thermal conditions between land and sea, leading to an intensification of monsoon winds and above-normal rainfall over India. Recent paleoclimate evidence confirms this, suggesting that during periods of high total solar irradiance, the ENSO-ISM correlation is strengthened and the ENSO-EASM correlation is weakened (Du et al, 2023). In addition, Narasimha and Bhattacharyya (2010) showed ENSO connections with solar activity, and suggested that the influence of solar irradiance on the ISM is indirectly applied via the ENSO teleconnection.…”
mentioning
confidence: 79%